Ecology of a typical West African Sudanian savannah rodent community. (6th December 2012) - Bâ, Khalilou; Kane, Mamadou; Gauthier, Philippe; Granjon, Laurent
Abstract: The small‐mammal community of a typical Sudanian savannah area of south‐eastern Senegal was studied by way of intensive sampling at the beginning (July) and at the end (November) of the rainy season. A total of 5931 trapnights and 200 pitfallnights yielded 767 small mammals, including 757 rodents of 12 species, as well as a few shrews and hedgehogs. Accumulation curve indicated that the rodent community was well sampled. Murine rodents were far more numerous than gerbilline rodents, and among them, Mastomys erythroleucus was the dominant species, being caught in high numbers in all habitats. Arvicanthis niloticus and Praomys daltoni were also abundant, followed by Mastomys natalensis and Gerbilliscus guineae . Abundances were high at the beginning of the rainy season when reproductive activity was low in all species. At the end of the rainy season, murine rodents were actively involved in reproduction, while gerbilline rodents were at their lowest density. Significant changes in relative abundance among habitats (including human dwellings) were observed between periods in some species, suggesting seasonal trends in habitat preferences. This may help species coexistence in this species‐rich rodent community, in an area likely to be submitted to significant habitat alterations in the years to come.